2020
DOI: 10.37190/ord200301
|View full text |Cite
|
Sign up to set email alerts
|

Simulation modeling for predicting hospital admissions and bed utilisation

Abstract: Demographic research of world population shows that societies are ageing. The ongoing changes in the population structure will require appropriate quantitative and qualitative adjustments in health services to meet the needs of society. Simulation methods turn out to be helpful in these kinds of analyses. In this paper, the authors present a case study on using discrete event simulation (DES) to support decision-making in the field of hospital bed management in the light of demographic changes. The case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Simulation models have been widely used in research articles focusing on hospital bed management (Ahmad et al, 2014;Clissold et al, 2015;Hajlasz & Mielczarek, 2020;He et al, 2019;Helbig et al, 2015;Holm et al, 2013;Khanna et al, 2016;Landa et al, 2017;Mallor & Azcarate, 2014;Monks et al, 2016;Oliveira et al, 2020;Qin et al, 2017;Seymour et al, 2015;Varney et al, 2019). These computer-based tools mimic real-world systems and processes and are particularly useful for predicting and analyzing patient flow and resource utilization in hospital settings.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation models have been widely used in research articles focusing on hospital bed management (Ahmad et al, 2014;Clissold et al, 2015;Hajlasz & Mielczarek, 2020;He et al, 2019;Helbig et al, 2015;Holm et al, 2013;Khanna et al, 2016;Landa et al, 2017;Mallor & Azcarate, 2014;Monks et al, 2016;Oliveira et al, 2020;Qin et al, 2017;Seymour et al, 2015;Varney et al, 2019). These computer-based tools mimic real-world systems and processes and are particularly useful for predicting and analyzing patient flow and resource utilization in hospital settings.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…By analyzing historical bed occupancy data and using a weekly time horizon, the authors propose policies to reduce congestion and improve the quality of care. Hajlasz and Mielczarek (2020) conducted a case study using discrete event simulation to predict hospital admissions and bed utilization in a Polish district hospital. The study found that a 6% reduction in admissions to the pediatric ward resulted in a decrease in average bed utilization from 57.90% to 54.06%, while a 12% increase in admissions to the geriatric ward led to an increase in bed utilization from 68.88% to 75.59%.…”
Section: Theoretical Frameworkmentioning
confidence: 99%